The Effect of Self Management Through Family E - Coaching on Decreased Blood Glucose Levels in Diabetes Mellitus Patients - Handayani, Tut; Indargairi, Indargairi; Alamsyah, Alamsyah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
The purpose of this study was to determine the effect of self-management with family coaching on reducing blood glucose levels in patients with diabetes mellitus. This study used a quantitative method with a pre-experimental approach with a total sample of 30 people using a purposive sampling technique. The results of this study indicate that self-management with family coaching contributes to a decrease in blood glucose levels in diabetes mellitus patients with a significant value of p = 0.000 > 0.05. It can be concluded that self-management with family e coaching has an effect on reducing blood glucose levels in patients with diabetes mellitus. For future researchers, it is hoped that they can develop Android-based applications for family e-coaching.